Associations Between Sad Feelings and Suicide Behaviors in the 2019 Youth Risk Behavior Survey: A Call for Action - Trimble, Deana G.; Chandran, Aruna (Frontiers in Pediatrics, 2021)
Purpose Suicide is the second leading cause of death among high school aged students in the United States. Significant risk factors for suicidal behaviors among youth include diagnoses of depression or other mental illnesses. The association between self-reported sad feelings and suicidal behaviors has been understudied in the literature among United States high school students. Methods The 2019 National Youth Risk Behavior Survey (YRBS) school-based questionnaire, coordinated by the CDC, captured a nationally-representative sample (N=13,677) of students’ responses to health-related behaviors. National sex-stratified prevalences of sad feelings and suicidal behaviors were calculated. Adjusted weighted logistic regression was used to examine the association between self-reported sad feelings and suicidal behaviors. Results Out of 13,677 high-school students, 35.8% of students self-reported sad feelings. Suicidal behaviors in the overall sample included 18.2% had seriously considered suicide, 15.2% made a plan on how they would attempt suicide, and 7.3% attempted suicide within the past 12 months. There was an 8-11 fold increased odds of all suicidal behaviors among those who reported sad feelings among both females and males. Conclusions This study reveals a remarkably high prevalence of sad feelings among US youth, and underscores a significant association between self-reported sad feelings and suicidal behaviors among this population. The YRBS survey, routinely administered across US high school students, should be better leveraged to target interventions towards these high-risk youth in order to decrease the significant burden of suicidal behaviors among adolescents.